MODEL-MODEL HUBUNGAN MASYARAKAT DI LEMBAGA PENDIDIKAN ISLAM - Eko Wahyudi (Melati Institute, 2023)
This study focused on the development of science and technology can give these demands make college need the model of public relations to develop the college the purpose of research is 1) Press agentry / publicity model is a model where information moves in one direction, from organization to public. This model is the oldest form of public relations and this model has the same meaning as promotion and publicity. Public relations practitioners who practice this model are always looking for opportunities to get their organization's good name to appear in the media.2) Public Information Model. This model is different from press agentry, because the main purpose is to notify the public and not for promotion and publicity, but the communication path remains one way.3) Model Two-way Asymmetric Model. This model views public relations as a work of scientific persuasion. This model applies social science research methods to improve the effectiveness of persuasion of the messages conveyed. Public relations practitioners with this model use surveys, interviews, and focus groups to measure and assess the public so that they can design public relations programs that can gain support from key public.4) Two-way symmetric model. This model describes a public relations orientation in which organizations and the public adapt to each other. This model focuses on the use of social science research methods to gain a sense of mutual understanding and two-way communication between the public and the organization rather than one-way persuasion.Of the four models, which should be developed by Islamic educational institutions is a two way symmetric model. This is because this model holds a reciprocal relationship between Islamic educational institutions and the community.so, the model of public relations model in educational institutions of the college is very important.